Calc-silicate rocks and marbles from Lutzow-Holm Complex,East Antarctica, with special reference to the mineralogy and geochemical characteristics of calc-silicate mega-boudins from Rundvagshetta - Satish-Kumar, M.; Motoyoshi, Yoichi; Suda, Yoshimitsu; Hiroi, Yoshikuni; Kagashima, Shin-ichi (National Institute of Polar Research, 2006)
P(論文) We report here the mode of occurrence of calc-silicate rocks and marbles from the Lutzow-Holm Complex, East Antarctica, and a worked example from Rundvagshetta. Calc-silicate boudins were observed in Cape Hinode, Akarui Point, Byobu Rock, Skarvsnes, Skallevikshalsen and Rundvagshetta, whereas they were reported earlier from Sinnan Rock, Cape Ryugu, Akebono Rock, Cape Hinode, Niban Rock, Kasumi Rock, Daruma Rock, Cape Omega, Langhovde, Ytrehovdeholmen and Skarvsnes. They vary in size from decimeters to few meters and are commonly enclosed within pelitic or psammitic gneisses. In addition, extensive layers of marbles and calc-silicate rocks are distributed in Skallevikshalsen. The calc-silicate mega-boudins within the layered pyroxene-gneiss from Rundvagshetta, up to 5m long and 2m thick, comprises of coarse to medium grained assemblage of scapolite+anorthite+garnet+clinopyroxene+calcite+quartz+titanite±wollastonite. Co-existing scapolite and plagioclase suggest a "minimum" estimate of peak metamorphic temperature of ～830°C . Peak metamorphic mineral assemblages equilibrated at moderate to high X_(CO2) conditions (0.3-0.7) and temperatures between 850 and 1000°C , consistent with the ultrahigh temperature metamorphic conditions reported in the region. Multistage garnet corona formation preserved in the calc-silicate assemblage suggests a local increase in hydrous fluid activity during retrogression. Preliminary bulk rock geochemistry of different mineralogical zones in the boudin shows chemical potential gradients in some major elements, especially SiO_2, Al_2O_3 and CaO, possibly controlled by the compositional variations in the protolith. Altogether, these results suggest that calc-silicate rocks preserve information on the metamorphic evolution and help us in deducing the geodynamic evolution of high-grade terrains. departmental bulletin paper